2007
DOI: 10.1111/j.1600-0528.2007.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dental status and dental care utilization in the Swedish population over three decades: age, period, or cohort effects?

Abstract: For both edentulousness and dental care utilization, almost all variation originated before 1968. These cohort effects are probably the consequences of changes in dentistry going back several decades and they demonstrate the early socialization of health behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 19 publications
3
47
1
3
Order By: Relevance
“…As the older population in Sweden and in other developed countries increases, so does the need for dental and medical care for this population (Hugoson et al 2005, Ahacic & Thorslund 2008. Nursing home resident older people often have their own teeth or fixed prosthetic appliances (e.g.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…As the older population in Sweden and in other developed countries increases, so does the need for dental and medical care for this population (Hugoson et al 2005, Ahacic & Thorslund 2008. Nursing home resident older people often have their own teeth or fixed prosthetic appliances (e.g.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In another study we have discussed more elaborately the changes in edentulousness as well as changes in dental care services (Ahacic and Thorslund 2006). This study suggested that cohort eVects dominate not only dental status but also dental care.…”
Section: Ormentioning
confidence: 99%
“…Embora a provisão de fatores relacionados à infraestrutura de serviços de saúde seja considerada importante determinante da sua utilização 13 , tal relação não está claramente estabelecida. Estudos internacionais encontraram resultados contraditórios na relação entre uso de serviços odontológicos e o incremento da oferta 14,15,16,17,18 . Por exemplo, apesar do aumento de acesso ao dentista, houve um declínio na utilização de serviços odontológicos por parte dos jovens brasileiros, nas capitais, durante o período de 1986 a 2002, possivelmente por melhorias nas condições de saúde bucal 18 .…”
Section: Introductionunclassified
“…Por exemplo, apesar do aumento de acesso ao dentista, houve um declínio na utilização de serviços odontológicos por parte dos jovens brasileiros, nas capitais, durante o período de 1986 a 2002, possivelmente por melhorias nas condições de saúde bucal 18 . Há evidências de que expansão ou contração de oferta não altera o uso dos serviços odontológicos, uma vez que ele parece sofrer forte influência de efeito de coorte de nascimento 17 . Alguns estudos mostram que com a expansão de serviços gratuitos de atenção primária, as pessoas em menos desvantagem utilizam mais os serviços 19,20 .…”
Section: Introductionunclassified